Elevated Serum Uric Acid to HDL-Cholesterol Ratio is Related to Cardiovascular Risk in Patients Receiving Hemodialysis - Lütfullah Altıntepe; Yasemin Coşkun Yavuz; Zeynep Bıyık; Hilal Akay Çizmecioglu; Mevlüt Hakan Göktepe; Ahmet Cizmecioglu (Genel Tıp Dergisi)
Aim: Chronic kidney disease (CKD) is a progressive disease in which frequent cardiovascular (CV) comorbidities. High uric acid to HDL-cholesterol ratio (UHR) results were quite notable in patients receiving peritoneal dialysis. Thus, in this study, we aimed to evaluate the UHR results in dialysis patients. Materials and Methods: This retrospective, multicenter, cross-sectional study was conducted with CKD patients, and the control group consisted of hypertensive patients with a normal glomerular filtration rate (GFR). Patients’ laboratory, ambulatory blood pressure monitoring, and demographic records were obtained from the follow-up cases of two university hospitals’ internal medicine and nephrology departments. The patients' group then were divided into five subsets according to GFR. Results: A total of 124 CKD patients and 127 control participated in this study. All CKD patients were also identified as pre-dialysis and dialysis. The cases of UHR, non-dipper blood pressure pattern, and nocturnal heart rate (HR) were increased in CKD compared to the control group. Per disease progression, the non-dipper HR and nocturnal HR were more significant in patients receiving dialysis with high UHR than in the pre-dialysis subset. In diabetic patients with an on-targeted HbA1c, those with high UHRs still had nocturnal diastolic BP elevations. Finally, there was not an exact stage-specific result for pulse wave velocity. Conclusions: Based on our results, dialysis patients with high UHRs have higher non-dipper PR, nocturnal heart rate, and nocturnal diastole blood pressure, associated with CV risk. Moreover, effective diabetic management might not prevent CV risk in dialysis patients with high UHRs.